Model to Assess the Exhaust Emissions from the Engine of a Small Aircraft During Flight. (2017) - Markowski, Jaroslaw; Pielecha, Jacek; Jasiński, Remigiusz
Abstract: Evaluation of the exhaust emissions from aircraft engines applies to turbine engines with high values of thrust and power. This assessment is conducting on the basis of the guidelines contained in the standards introduced by ICAO Annex 16. It concerns the procedure for stationary tests according to the Landing/Take-off cycle (LTO). This test includes operating parameters of the engine corresponding to approach, landing, airport operations and take-off. Such procedures do not apply to small aircraft with piston engines. Therefore, a number of research and testing of exhaust emissions from aircraft piston engines were made. On the basis of these works, model to determine the exhaust emissions from piston engines during the flight of the aircraft was developed. The model is presented in this article.